Importance of transport security in the realization of Russia’s national interests - A. M. Novozhilov (Путеводитель предпринимателя, 2020)
Only the presence and intensive development of the transport infrastructure in the Russian Federation, including all existing modes of transport, including road, rail, air, inland water, sea, other modes of transport, can ensure the sustainable development of the country, primarily its economic system, guarantee unimpeded movement of people and goods across Russia.